Spatial and Temporal Variation of Main Air Pollutants and Their Concentrations in Relation to Meteorological Conditions in the Industrialized City of Kocaeli - Burak Kotan; Arzu Erener (Coğrafya Dergisi)
Air pollution monitoring, continuous monitoring, and evaluation are critical in terms of decreasing and mitigating the consequences of air pollution on humans, living things, and the environment. Information technology-based analyses are quite effective to this aim. In this work, the temporal and spatial changes of air pollution in Kocaeli, an industrial city, were examined and mapped seasonally for 2008, 2014, and 2019. The study used data for the air contaminants PM10 and SO2. For places where measurements could not be made from the available data, the interpolation approach was used to generate concentration values. One of the interpolation methods employed was the inverse distance weighted technique (IDW). Pollution maps for the winter, spring, summer, and fall seasons of 2008, 2014, and 2019 were developed for Kocaeli by providing data continuity with the produced values. With the help of geographic information systems technology, overlay analysis was performed on the maps, and seasonal changes between years were observed. In this context, 2014 was compared to 2008 and 2019 was compared to 2014. As a result, despite a drop in concentration values from 2008 to 2019, it has been established that there are local regions in Kocaeli that exceeded the European Union’s and national pollutant concentration limit values in the year 2019.